Implementation Science Strategies Promote Fidelity in the Food, Feeding, and Your Family Study. - Aragón, M. Catalina; Auld, Garry; Baker, Susan S.; Barale, Karen V.; Garcia, Karina Silva; Micheli, Nilda; Parker, Louise; Lanigan, Jane D.; Power, Thomas G.; Hughes, Sheryl O. (Journal of Nutrition Education & Behavior, 2021)
Use of implementation science strategies to promote fidelity in the Food, Feeding, and Your Family study. Cluster randomized controlled trial with 3 conditions: control, in-class, or online, delivered in English or Spanish. Observations of 20% of classes. Expanded Food and Nutrition Education Program (EFNEP) in 2 states. EFNEP peer educators (n = 11). Parental feeding content incorporated into EFNEP lessons (in-class) or through text with links to videos/activities (online). Extensive educator training, scripted curriculum, frequent feedback. Assessment of fidelity compliance. Qualitative analysis of verbatim educator interviews and classroom observer comments. During 128 class observations (40–45 per condition), peer educators followed scripted lesson plan 78% to 89% of the time. There was no evidence of cross-contamination of parental feeding content in control and only minor sharing in online conditions. Variations with fidelity were primarily tied to the EFNEP curriculum, not the parent feeding content. Educators (n = 7) expressed favorable opinions about the Food, Feeding, and Your Family study, thought it provided valuable information, and appreciated support from EFNEP leadership. Incorporating implementation science strategies can help ensure successful adherence to research protocols. With proper training and support, EFNEP peer educators can deliver an evidence-based curriculum as part of a complex research study.